2020
DOI: 10.3390/ijms21155261
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Epoxydocosapentaenoic Acid Analogue Ameliorates Cardiac Ischemia/Reperfusion Injury: The Involvement of the Sirtuin 3–NLRP3 Pathway

Abstract: While survival rates have markedly improved following cardiac ischemia-reperfusion (IR) injury, the resulting heart damage remains an important issue. Preserving mitochondrial quality and limiting NLRP3 inflammasome activation is an approach to limit IR injury, in which the mitochondrial deacetylase sirtuin 3 (SIRT3) has a role. Recent data demonstrate cytochrome P450 (CYP450)-derived epoxy metabolites, epoxydocosapentaenoic acids (EDPs), of docosahexaenoic acid (DHA), attenuate cardiac IR injury. EDPs undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Bianca et al [ 33 ] suggested that HCY exerted a prothrombotic effect by enhancing platelet aggregation. Several studies also showed that HHCY might enhance the adverse effects of CAD risk factors such as essential hypertension, smoking, dyslipidemia, and diabetes mellitus [ 34 37 ]. These were probably related to the formation and progression of CAD in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Bianca et al [ 33 ] suggested that HCY exerted a prothrombotic effect by enhancing platelet aggregation. Several studies also showed that HHCY might enhance the adverse effects of CAD risk factors such as essential hypertension, smoking, dyslipidemia, and diabetes mellitus [ 34 37 ]. These were probably related to the formation and progression of CAD in young adults.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there is growing interest in ω-3 EpFAs, namely Eicosapentaenoic acid (EPA, 20:5)-derived Epoxyeicosatetraenoic acids (EEQs) and Docosahexaenoic acid (DHA, 22:6)derived Epoxydocosapentaenoic acids (EDPs), and their synthetic analogues. [29][30][31] Thus, as a possible next step, the alkoxy-mimics of these EpFAs could also be examined, especially since EEQs and EDPs have in fact proven to be more potent than EETs in certain disease models. 32,33 26 Finally, activity of individual regioisomers within the most promising series could potentially be explored, with particular emphasis being placed on molecules with functional groups positioned at the terminal olefin, since these have generally proven to be the most biologically relevant within each of the three EpFA series.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, there is growing interest in ω-3-EpFAs, namely, eicosapentaenoic acid (EPA, 20:5)-derived epoxyeicosatetraenoic acids (EEQs) and docosahexaenoic acid (DHA, 22:6)-derived epoxydocosapentaenoic acids (EDPs), and their synthetic analogues. Thus, as a next step, the alkoxy- analogues of these EpFAs could also be examined, especially since EEQs and EDPs are more potent than EETs in certain disease models. , Moreover, activity of individual regioisomers within the most promising series should eventually be explored.…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3 mainly localizes in the endoplasmic reticulum in the resting state, while NLRP3 and its adaptor ASC are redistributed to the perinuclear space during inflammasome activation, where they co-localize with mitochondria-associated endoplasmic reticulum and are involved in recruiting and activating pro-caspase-1 into caspase-1 ( 5 ). The activated caspase-1 then promotes the maturation and release of interleukin (IL)-1β and IL-18, and induces the synthesis of more amount of inflammatory factors, such as IL-6 and tumor necrosis factor (TNF)-α, thus leading to an inflammatory cascade response ( 15 , 16 ). Moreover, activated caspase-1 can shear and activate Gasdermin D (GSDMD) protein, causing pyroptosis and aggravating mitochondrial damage ( 17 ).…”
Section: Introductionmentioning
confidence: 99%